Influence of hyperprolactinemia on collagen fibers in the lacrimal gland of female mice (Clinics, 2015)
OBJECTIVE:To quantify the collagen fibers in the lacrimal gland of female mice with hyperprolactinemia.METHODS:Forty adult female mice were randomly divided into two groups with 20 animals each: nonpregnant control (CTR1, control group, 0.2 mL of saline solution) and nonpregnant experimental (HPRL1, experimental group, 200 µg/day metoclopramide). Treatments lasted for 50 consecutive days. On day 50, 10 females from each group (control and experimental) were euthanized in the proestrus phase; then, the blood was collected and the lacrimal glands were removed. Thereafter, the remaining females were placed with the mates and continued to receive treatment with saline solution or metoclopramide. On the 6th post-coital day, 10 pregnant females from the control group (CTR2) and 10 pregnant females from the experimental group (HPRL2) were euthanized, after which blood was collected and the lacrimal glands removed. The lacrimal glands were processed for morphological analyses and collagen quantification, and prolactin and sex steroid levels were measured in the blood samples. Data were statistically analyzed using an unpaired Student t test (p